Exploring Formal and Non-formal Education Practices for Integrated and Diverse Learning Environments in Uganda - Ngaka, Willy; Openjuru, George; Mazur, Robert E. (The International Journal of Diversity in Organizations, Communities and Nations, 2012)
This paper explores opportunities for integrating formal and non-formal education in Uganda in ways that help learners acquire, build and maintain productive skills for sustainable livelihoods. Using an interpretive paradigm, the authors draw on the capability approach and social practices theory of literacy to guide their qualitative analysis. The authors describe good practices in nonformal education in Uganda and Africa which diversify learning options for learners. Integration of formal and non-formal education is shown as capable of promoting practice-oriented skills learning which can significantly improve Uganda’s education system which is currently too theoretical for addressing people’s real needs. Such integration can maximize rural people’s participation levels in government’s poverty reduction interventions and enhance their chances for creating wealth and attaining sustainable livelihoods. Challenges to be faced in bridging the gap between the two forms of education in Uganda are highlighted and the way forward suggested.
Keywords: Education; Formal Education; Indigenous Education; Informal Education; Lifelong Learning; Non-formal Education; Wealth